AB0207 Change in anti-citrullinated protein autoantibody levels in clinical practice are associated with resource use and disease activity measures. (15th June 2017) - Alemao, E; Guo, Z; Iannaccone, C; Frits, M; Shadick, N; Weinblatt, M
Abstract : Background: High anti-citrullinated protein antibody (ACPA) concentration, beyond ACPA positivity, is indicative of more aggressive radiographic progression in patients (pts) with RA. 1 However, there is limited information on changes in ACPA levels in clinical practice settings, and the association of changes in ACPA with measures of resource use and/or disease activity. Objectives: To evaluate the association between change in ACPA levels with hospitalizations/durable medical equipment (DME) use and change in disease activity. Methods: Pts enrolled in a tertiary care centre RA registry, established in 2003, were analysed. The registry mostly comprises pts with established RA who were evaluated semi-annually for multiple clinical patient-reported outcomes as well as resource utilization parameters, and annually for disease activity measures such as DAS28 (CRP), SDAI and CDAI. The current analysis is based on pts enrolled in the registry with ACPA values at the time of baseline (BL) and follow-up visits. BL and follow-up ACPA levels were based on well-documented and validated ELISAs from Euro-Diagnostica (distributed by IBL-America, Minneapolis, MN, USA). Annual mean ACPA change from BL over the first year of enrolment in the registry was calculated. Changes ([follow-up – BL]/BL x 100) in ACPA levels were categorized as decrease (<–10%), no change (–10% to +10%) or increase (>+10%). Use of DME (canes, wheelchairs, walkers and commodes) as well as hospitalizations during 12-month follow-up and annual change in disease activity (DAS28 [CRP], SDAI, CDAI, swollen painful joint counts and pain) were assessed. Multivariate logistic regression analyses for binary outcome variables (DME and hospitalizations) and linear regression for change in disease activity measures were conducted, controlling for BL covariates. Results: A total of 840 (65%) pts in the registry had BL and follow-up ACPA values and were included in the analysis. Overall, 34.6% (n=291) of pts had a decrease, 31.7% (n=266) had no change and 33.7% (n=283) had an increase in ACPA levels. There were no significant differences in BL characteristics between the three groups except for disease duration. Pts with RA with an increase in ACPA levels had significantly longer disease duration at BL. In univariate analyses, DME use was 23.4%, 30.1% and 28.6%, and hospitalization rate was 13.4%, 16.5% and 20.1% in pts with a decrease, no change or an increase in ACPA levels, respectively. Unadjusted mean (SD) change from BL in DAS28 (CRP), SDAI and CDAI in pts with reductions in ACPA levels was –0.7 (1.4), –6.1 (15.7) and –5.9 (15.1), and –0.5 (1.4), –5.0 (15.7) and –4.7 (14.6) in pts with an increase in ACPA levels. After controlling for BL covariates, the odds ratio (OR) for DME in patients who had a decrease in ACPA levels (vs increase) was 0.62 (95% CI 0.40, 0.94; p=0.026), and the OR for hospitalization was 0.54 (0.33, 0.86; p=0.010). Similarly, reductions in ACPA levels were associated with greater reductions in disease activity measures (Fig). Conclusions: Reductions in ACPA levels were associated with reductions in DME use and hospitalizations as well as reductions in disease activity measures. References: Ronnelid J, et al. Ann Rheum Dis 2005;64:1744–9. Disclosure of Interest: E. Alemao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Z. Guo Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, C. Iannaccone: None declared, M. Frits: None declared, N. Shadick Grant/research support from: Bristol-Myers Squibb, UCB, Mallinckrodt, Amgen, Crescendo Biosciences, Consultant for: Bristol-Myers Squibb, M. Weinblatt Grant/research support from: Amgen, Bristol-Myers Squibb, Crescendo, UCB, Dxterity, Consultant for: Amgen, Bristol-Myers Squibb, Crescendo Biosciences, UCB, AbbVie, Lilly, Pfizer, Roche